Qaḍā’ dan Qadar: Diskursus Pemikiran Jabariyah dan Qadariyah - Mujtaba, M. Shohibul; Zarkasyi, Amal Fathullah; Falah, Muhammad Zulfikar Nur (Universitas Islam Negeri Raden Intan Lampung, 2025)
Abstract This research discusses Jabariyah and Qadariyah thoughts in the qaḍā' and qadar discourse. The skewed implications of the concepts of qaḍā' and qadar from the Jabariyah and Qadariyah discourses are a problem in this research. The difference with previous studies is that it places more emphasis on discourses of thought that develop epistemologically. This research method is library research using a descriptive analysis approach. The findings of this research show that Jabariyah thinking in matters of qaḍā' and qadar leads to placing humans bound by the will of Allah. Qadariyah thinking in matters of qaḍā' and qadar leads to placing humans separately from the will of Allah. The synthesis of Jabariyah thought discourse as thesis and Qadariyah thought as the antithesis is Allah determines human destiny from the very beginning, but humans also have a role in making it happen through effort. The recommendation on the findings of this study has implications for subsequent studies, namely not only analyzing the conceptual aspects of a problem, but emphasizing the analysis of applicable ideas to address the problem comprehensively. Keywords: Free Will; God’s Will; Jabariyah; Qadariyah; Qaḍā’ and Qadar